If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = p + 5 Reorder the terms: 11 = 5 + p Solving 11 = 5 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 11 + -1p = 5 + p + -1p Combine like terms: p + -1p = 0 11 + -1p = 5 + 0 11 + -1p = 5 Add '-11' to each side of the equation. 11 + -11 + -1p = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -1p = 5 + -11 -1p = 5 + -11 Combine like terms: 5 + -11 = -6 -1p = -6 Divide each side by '-1'. p = 6 Simplifying p = 6
| 1/3h-42/3h-3=2/3h-6 | | .06x=20 | | 8x+40=x | | 22x-16=4+65 | | 2x+7(-x-1)=2 | | 11z=12z-28 | | x^2+7x-2=6x | | -5(-5x-5)-2x+1=-7 | | X(X-3)=80 | | Z+1.8=7.4 | | x=.94x+102 | | -3-2*-6= | | 2(x+2)=-4-2x | | (2x-3)/18-(x-4)/6=1/9 | | 3x^2+36+81=0 | | -7r+4=18 | | z+49=15 | | 2x+7(-x+1)=2 | | -7r+4=17 | | 3x^3+36+81=0 | | 82x+47=75x+166 | | 3sinx=-3 | | 400-4x=20 | | 0.22=0.7+0.5m | | 4yx+5x=y | | -5(-2x-3)-3x-4=-38 | | 9a+3b-8(9a-2b)= | | 0.22=0.7+0.5 | | 82x+47=57x+166 | | 5(x+1)-1=21 | | -6+2n+15=-7n | | 34-5x+2(x-3)=15 |